Simple, streamlined, cost-effective cDNA synthesis method from cell cultures - Stránský, Daniel; Šteigerová, Monika; Kuklová, Markéta; Hanzíková, Veronika; Canová, Nikolina; Novotný, Jiří; Šenolt, Ladislav; Slanař, Ondřej (Open biology, 2025)
Applications like drug development need simple and streamlined methods to process samples from 96-well cell culture plates for gene expression measurements. Unfortunately, current options are expensive for such processing. Therefore, our aim was to develop a method that would allow streamlined analysis of mRNA from 96-well cell culture plates while being relatively cheap and simple. We developed a method based on the qPCR 'Cells-to-cDNA' approach and validated it against commercially available kits using the same approach or spin columns-based RNA purification. For this purpose, we conducted a series of comparisons of gene expression from peripheral blood mononuclear cells, SK-HEP-1 and U-87 cell cultures in 96-well plates. Our final method involved lysing cells with 25-100 μl solution of 0.5% SDS, 10 mM DTT, 1 mg ml-1 proteinase K dissolved in water, 1 h incubation at 50°C, followed by proteinase K inactivation at 90°C for 5 min and lysate neutralization with 1 : 1 dilution by 20% Tween 20 solution. Reverse transcription and qPCR were carried out using standard methods. This method showed a mean reduction of Ct ± s.d. value by 2.4 ± 1.3 compared with the 'Cells-to-cDNA' kit and by 1.4 ± 0.5 compared with the RNA purification kit with lower variability.
Keywords: Humans; Cell Culture Techniques; Cell Line, Tumor; buněčné kultury; kvantitativní polymerázová řetězová reakce; leukocyty mononukleární; messenger RNA; Real-Time Polymerase Chain Reaction; Gene Expression Profiling; DNA, Complementary; nádorové buněčné linie; komplementární DNA; RNA, Messenger; Leukocytes, Mononuclear; Cost-Benefit Analysis; analýza nákladů a výnosů; stanovení celkové genové exprese; lidé